Natural soil microbes alter flowering phenology and the intensity of selection on flowering time in a wild Arabidopsis relative. (4th April 2014) - Wagner, Maggie R.; Lundberg, Derek S.; Coleman‐Derr, Devin; Tringe, Susannah G.; Dangl, Jeffery L.; Mitchell‐Olds, Thomas; Klironomos, John
Abstract Plant phenology is known to depend on many different environmental variables, but soil microbial communities have rarely been acknowledged as possible drivers of flowering time. Here, we tested separately the effects of four naturally occurring soil microbiomes and their constituent soil chemistries on flowering phenology and reproductive fitness of Boechera stricta, a wild relative of Arabidopsis. Flowering time was sensitive to both microbes and the abiotic properties of different soils; varying soil microbiota also altered patterns of selection on flowering time. Thus, soil microbes potentially contribute to phenotypic plasticity of flowering time and to differential selection observed between habitats. We also describe a method to dissect the microbiome into single axes of variation that can help identify candidate organisms whose abundance in soil correlates with flowering time. This approach is broadly applicable to search for microbial community members that alter biological characteristics of interest.